Experimental investigation on a dual-mode seasonal solar thermochemical sorption energy storage system - Li, T.X.; Wu, S.; Yan, T.; Wang, R.Z.; Zhu, J. (Elsevier, 2017)
A dual-mode seasonal solar thermochemical sorption energy storage system using working pair of expanded graphite/SrCl2-NH3 was constructed and investigated. Solar thermal energy is transformed into chemical bonds in summer, and the stored energy is released in the form of chemical reaction heat in winter. Two working modes are performed to produce heat with expected temperature according to the different ambient temperatures in winter. The direct heating supply mode is adopted at a relatively high ambient temperature. The effective energy storage density is higher than 700kJ/kg and the corresponding system COP is 0.41 when the heat output temperature and ambient temperature are 35oC and 15oC, respectively. The specific heating power increases with the decrease of heat output temperature for a given ambient temperature. The temperature-lift heating supply mode is adopted to upgrade the heat output temperature at a low ambient temperature below 0oC. It can produce heat with a temperature above 70 oC although the ambient temperature is as low as -15oC. It is desirable to further improve the system performance using low mass ratio and high global conversion. Experimental results showed the advanced dual-mode thermochemical sorption energy storage technology is feasible and effective for seasonal solar thermal energy storage.